مستوى التوافق النفسي لدى أشقاء المعاقين ذهنيا حسب إدراكهم للإعاقة - بكار، بلقيس (جامعة الوادي university of Eloued, 2017)
ملخص الدراسة: هدفت الد ارسة الحالية التعرف على مستوى التوافق النفسي لدى أشقاء المعاقين ذهنيا وفق إد اركهم للإعاقة ومعرفة ما إذا كان هناك فروق في مستوى التوافق تبعا لمتغير الجنس (إناث- ذكور) وتبعا لمتغير المستوى الد ارسي(الجامعي- دون الجامعي) وتبعا لمتغير الحالة الاقتصادية(مقبول ضعيف) وتبعا لمتغير شدة الاعاقة(شديدة- ضعيفة). ولتحقيق أهداف الدراسة تم الاعتماد على مقياس التوافق النفسي وفق ادراك الاعاقة موجهة لأشقاء المعاقين ذهنيا والذي تكون من ( )43بند، تم اعدادهما من طرف الطالبة وتوزعت هذه البنود على بعدين، البعد الشخصي للتوافق، والبعد الاجتماعي للتوافق، وتكونت عينة الدراسة من 75شقيقا لأفراد مصنفين أنهم معاقين ذهنيا، وبإتباع المنهج الوصفي بأسلوبه الاستكشافي، واستخدام الأساليب الاحصائية المتمثلة في المتوسط الحسابي الانح ارف المعياري، اختبار"ت" لدلالة الفروق بين المتوسطات تم التوصل إلى النتائج التالية: لا توجد فروق ذات دلالة احصائية في مستوى التوافق لدى أشقاء المعاقين عقليا تبعا لمتغير الجنس(إناث- ذكور) عند مستوى دلالة (.)...7 لا توجد فروق ذات دلالة احصائية في مستوى التوافق لدى أشقاء المعاقين عقليا تبعا لمتغير المستوى الد ارسي(جامعي- دون الجامعي) عند مستوى دلالة (.)...7 لا توجد فروق ذات دلالة احصائية في مستوى التوافق لدى أشقاء المعاقين عقليا تبعا لمتغير الحالة الاقتصادية(مقبول- ضعيف) عند مستوى دلالة (.)...7 لا توجد فروق ذات دلالة احصائية في مستوى التوافق لدى أشقاء المعاقين عقليا تبعا لمتغير شدة الاعاقة(ضعيفة- شديدة) عند مستوى دلالة (.)...7 إذن يمكن القول أن: مستوى التوافق النفسي لدى اشقاء المعاقين عقليا وفق إد اركهم للإعاقة يقع عند المستوى المرتفع.3 Abstract: The current study aimed at identifying the level of psychological compatibility among the mentally handicapped siblings according to their awareness of the disability and whether there were differences in the level of compatibility according to the gender variable (female - male) and according to the variable of the academic level (university –non university)depending on the variableof the economic situation(high-low) and according to the variable of the disability sever(sever-weak) . In order to achieve the objectives of the study, it was based on the measure of psychological compatibility according to the perception of disability directed to the mentally handicapped siblings, which consisted of (34) items, which were prepared by the student. These items were divided into two dimensions, the personal dimension of compatibility and the social dimension of compatibility. They are classified as mentally handicapped, following the descriptive approach in their exploratory approach, and using the statistical methods of the arithmetic average Standard Deviation, T Test To indicate the differences between the averages, the following results were obtained:  There were no statistically significant differences in the level of compatibility among siblings of the mentally disabled according to the gender variable (females - males) at the level of significance (0.05).  -There were no statistically significant differences in the level of compatibility among siblings of the mentally disabled according to the variable of the academic level (university - sub university) at the level of significance (0.05).  There were no statistically significant differences in the level of compatibility among siblings of the mentally disabled according to the economic situation variable (acceptable - weak) at the level of significance (0.05).  -There were no statistically significant differences in the level of compatibility among siblings of the mentally disabled according to the variable disability severity (weak - severe) at the level of significance (0.05).  It can therefore be said that: The level of psychological compatibility among the mentally disabled siblings according to their perception of disability is at a high level.
دراسة إستكشافية في بعض بلديات ولاية الوادي
مذكرة ماستر في علوم التربية تخصص التأهيل في التربية الخاصة
Keywords: التوافق النفسي، اللإعاقة العقلية; Compatibilité psychologique, handicap mental; Psychological compatibility, mental disability